Optimasi Kondisi Proses Pembuatan Manisan Kering Cabai Merah (Capsicum annuum L.) dengan Menggunakan Response Surface Methodology (RSM) - Hisworo Ramdani; Noli Novidahlia; Ulif Yuhana (JURNAL AGROINDUSTRI HALAL, 2018)
The aims of the research were to determine the optimum condition of  submerging time in 2% CaCl2 and various sugar solutions on sweetened dried red chili characteristics using Response Surface Methodology (RSM). Red chili were  submerged in 2% CaCl2 for 8, 10, 15, 20, and 22 minutes, and in 56%, 60% 70%, 80% and 84% sugar solutions.  The output combination of two factors are 13 run units.  The analysis included physics (color), chemical (moisture, vitamin C, total sucrose), hedonic test (color, taste, texture), descriptive test (color, sweetness, spiciness, texture).  The results showed that submerged time in 2% CaCl2 had significant effect on sweetness of sweetened dried red chili. The optimal condition processing of sweetened dried red chili was reached on combination of submerged time in 2% CaCl2 8 minutes and in 74% sugar solution with chroma 21.16, moisture 8.88 % db, vitamin C 9.34 mg/100 g, total sucrose  50°Brix,  hedonic score: color 5.03 (rather like), taste 4.43 (neutral), texture 4.42 (neutral), and descriptive sensory: color 5.24 (rather red), sweetness 4.05 (neutral), spiciness 5.05 (rather spicy), and texture 4.53 (rather rubbery).Keywords: optimization, sweetened, red chili, RSM